Prevalence of Food Myths and Beliefs among Pregnant Women of Haryana (International Journal of Food and Nutritional Sciences, 2022)
Pregnant women are the most vulnerable group of population. Pregnancy is a natural physiological state and during the course of evaluation adaptive mechanisms have developed to protect the fetus from harmful effects of adverse environmental conditions, including erratic supply of food conditions. Food myths are poorly justified nutritional concepts or even contradict existing scientific evidence, whereas individuals take them as the truth. Nutritional knowledge is an important tool in tackling misinformation and in the promotion of adequate food choices. The Present study was conducted to collect data about food myths and beliefs about pregnancy. One hundred twenty pregnant women were selected randomly from three hospitals, one is a private hospital (Bharat Nursing home) and two were government hospitals (Civil Hospital and PGI Rohtak). Questionnaire containing questions related to socio demographic information, food myths and beliefs was prepared and pretested. It was filled by an interview method. Study showed that food myths and beliefs were prevalent among Pregnant Women related to nutritive value, nature of foods and food myths and beliefs related to pregnancy which might have affected nutritional status. It can be concluded that nutrition education must be imparted to them to improve their nutritional status. Good nutrition during pregnancy will help to give birth to healthy babies, which is an asset for a developing nation.